Testosterone Promotes Glioblastoma Cell Proliferation, Migration, and Invasion Through Androgen Receptor Activation - Rodríguez-Lozano, Dulce Carolina; Piña-Medina, Ana Gabriela; Hansberg-Pastor, Valeria; Bello-Alvarez, Claudia; Camacho-Arroyo, Ignacio (Frontiers in Endocrinology, 2019)
Glioblastomas (GBM) are the most frequent and aggressive human brain tumors due to their high capacity to migrate and invade normal brain tissue. Epidemiological data report that GBM occur in a greater proportion in men than in women (3:2), suggesting the participation of sex hormones in the development of these tumors. It has been reported an increase in testosterone (T) levels in patients with GBM. In addition, androgen receptor (AR) is overexpressed in human GBM, and genetic silencing of AR, and its pharmacological inhibition, induce GBM cell death in vivo and in vitro. However, the role of T in proliferation, migration and invasion in human GBM cell lines has not been evaluated. We observed that T increased the number of U87, U251 and D54 cells derived from human GBM due to an increase in cell proliferation. This induction was blocked with flutamide, an antagonist of AR. T also induced migration and invasion of GBM cells that flutamide partially blocked. T reduces AR expression at 24 hours. These data suggest that T through AR contributes to the progression of GBM by promoting proliferation, migration and invasion.